Impact of leadless pacemaker implantation site on cardiac synchronization and tricuspid regurgitation - Xiao-fei Gao; Hong Zhu; Jia-sheng Zhang; Ning-Zhang; Xiao-hong Pan; Yi-Zhou Xu (The Egyptian Heart Journal)
Abstract Background To investigate the optimization of leadless pacemaker placement and to assess its impact on heart synchronization and tricuspid regurgitation. Results A clinical trial was conducted involving 53 patients who underwent leadless pacemaker implantation at the Second Affiliated Hospital of Zhejiang University School of Medicine and Hangzhou First People’s Hospital between March 2022 and February 2023. Implantation site localization was determined using the 18-segment method under RAO 30° imaging. Intraoperative and 1-month post-operative echocardiography was performed to assess cardiac electromechanical synchronization and tricuspid regurgitation; parameters of interest included interventricular mechanical delay (IVMD), pre-ejection period of the aorta (L-PEI), and septal-to-posterior wall motion delay (SPWMD). Pacing thresholds, sensing, and impedance exhibited no significant differences between the 8/9 zone and other sites (P > 0.05). In contrast, the 8/9 zone group manifested a significant reduction in L-PEI (128.24 ± 12.27 vs. 146.50 ± 18.17 ms, P < 0.001), IVMD (17.92 ± 8.47 vs. 28.56 ± 15.16 ms, P < 0.001), and SPWMD (72.84 ± 19.57 vs. 156.56 ± 81.54 ms, P < 0.001), compared to the non-8/9 group. Post-pacing QRS duration showed no significant difference between the two groups (139.21 ± 11.36 vs. 143.83 ± 16.35 ms P = 0.310). Notably, for patients with atrial fibrillation, the 8/9 zone placement significantly reduced tricuspid regurgitation. During the 1-month follow-up, neither group reported major complications such as bleeding, cardiac tamponade, pacemaker detachment, or malignant arrhythmias. Conclusion Implantation of the leadless pacemaker in the right ventricular 8/9 zone provides superior electromechanical synchronization compared to other sites.